1994
DOI: 10.1007/bf00010075
|View full text |Cite
|
Sign up to set email alerts
|

Subterranean clover decline in permanent pastures in north-eastern Victoria

Abstract: Experimental sites were established at two locations in north-eastern Victoria to define factors limiting the establishment and growth of Trifolium subterranean L. (subterranean clover). Liming the soil, seed inoculation and fungicide application were used in renovating subterranean clover pasture on two acidic soils (Longwood: brown/grey sandy loam DY 3.14 and Seymour: grey brown light clay DY 3.22, Northcote classification) with mean annual rainfall of 650 mm and 600 mm respectively. Soil acidity, low availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Aphanomyces euteiches Drechsler is an oomycete pathogen of legumes, which causes a devastating root rot of pea (Pisum sativum L.) worldwide (Kraft and Pfleger, 2001). Initially considered as a pea root pathogen (Scott, 1961), A.euteiches was later reported to attack other legume species such as common bean, broad bean, faba bean, clover, and alfalfa (Pfender and Hagedorn, 1982;Greenhalgh and Merriman, 1985;Lamari and Bernier, 1985;Tofte et al, 1992;Burnett et al, 1994;Tivoli et al, 2006;Moussart et al, 2008). The only two efficient ways to control the disease are diverse crop rotations with non-host or suppressive crops and breeding for resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Aphanomyces euteiches Drechsler is an oomycete pathogen of legumes, which causes a devastating root rot of pea (Pisum sativum L.) worldwide (Kraft and Pfleger, 2001). Initially considered as a pea root pathogen (Scott, 1961), A.euteiches was later reported to attack other legume species such as common bean, broad bean, faba bean, clover, and alfalfa (Pfender and Hagedorn, 1982;Greenhalgh and Merriman, 1985;Lamari and Bernier, 1985;Tofte et al, 1992;Burnett et al, 1994;Tivoli et al, 2006;Moussart et al, 2008). The only two efficient ways to control the disease are diverse crop rotations with non-host or suppressive crops and breeding for resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors also reported A. euteiches to be a pathogen of alfalfa ( Medicago sativa ) (Greenhalgh & Merriman, 1985), green bean ( Phaseolus vulgaris ) (Pfender & Hagedorn, 1982), broad bean ( Vicia faba ) (Lamari & Bernier, 1985) and clover ( Trifolium pratense , Tofte et al ., 1992; and Trifolium subterraneum , Burnett et al ., 1994). Many control measures have been tested (Papavizas & Ayers, 1974), but the only efficient way to control the disease identified to date is to avoid planting peas in contaminated fields and to ensure that there is an appropriate time interval between successive pea crops in the rotation (Carrouée et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude and prevalence of seedling losses indicated by the present results re‐emphasize the importance of treating pasture seeds with fungicide to maximize the establishment and yield of the sown species (Smiley et al. , 1986; Burnett et al. , 1994), even though it is known that fungicide treatments are usually only partially effective in controlling damping‐off and root disease (Barbetti et al.…”
Section: Discussionmentioning
confidence: 54%